Bowl‐Shaped Kekulene Analogues: Cycloarenes with two Five‐Membered Rings - Murakami, Hideyuki; Iwabuchi, Hiroki; Asari, Miki; Yamada, Hiroko; Kuzuhara, Daiki (Chemistry : a European journal, 2024)
Kekulene, a cycloarene composed of 12 fused benzene rings in a circular arrangement, exhibits a highly planar and robust structure. Kekulene has been the subject of investigation into its aromaticity and electronic structure, particularly in relation to the cyclic benzenoid. We have successfully synthesized novel bowl‐shaped kekulene analogues with five‐membered rings incorporated into the kekulene structure. The results of DFT calculations and VT‐NMR spectra indicate that inversion of their concave‐convex structures occurs at room temperature. The NICS and AICD plots predict that the Clar's type resonance structure is found in a manner analogous to the pristine kekulene, albeit with the interruption of the π‐conjugation on the sp3 carbons at the five‐membered rings. Despite the presence of the Clar's resonance structure, the Diels‐Alder reaction proceeded smoothly with a dienophile, in contrast to the behavior of planar kekulene derivatives. This study will lead to the creation of novel bowl‐shaped compounds and development of reactivity in aromatic compounds. Bowl‐shaped cycloarene have been synthesized via the introduction of five‐membered rings into the kekulene structure. The results of DFT calculations and VT‐NMR spectra indicate that inversion of concave‐convex structures occurs at room temperature. Additionally, these compounds react with a dienophile to produce the vent structure compounds.